Entomopathogenic Nematodes of Thrips Thripinema spp. (Nematoda: Tylenchida: Allantonematidae) - Danielle M. Sprague; Joseph E. Funderburk (EDIS)
Originally published on the Featured Creatures Website at http://entnemdept.ufl.edu/creatures/nematode/Thripinema_spp.htm